Assessment of Climate Variability on Poultry Production in Nigeria: 1990-2020 - Okuduwor; Oretan; Amadi-Robert; Johnson (International Journal of Integrative Sciences, 2023)
This study examined the influence of climate variability on poultry production in Nigeria from 1990-2020. State the broad objective only. This study adopted the quasi-experimental research design. Secondary data were used in the study. The method employed for analyzing the time series data was the Auto Regressive Distributed Lag (ARDL) model. Pre-estimation diagnostics tests were employed to check for stationarity of the data. From the results of the Error Correction Models (ECM’s), average rainfall and Carbon dioxide emission have significant influence on poultry (egg and meat) production in Nigeria. A unit increase in average rainfall brought about -0.4% reduction in egg production, while a unit increase in carbon dioxide emission brought about a -0.27% reduction in egg production. Average rainfall had positive influence on broiler production a unit increase in rainfall increased broiler production by 0.41% and 0.52% at the current and two period lag, while carbon dioxide emission reduced broiler production by -0.16%. The study concluded that climate change do affect poultry production both negatively and positively and recommended that climate smart agricultural practices such as proper ventilation and vaccination should be applied in poultry production to mitigate the negative effects of climate change